2017
DOI: 10.1007/s11224-017-1060-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly mechanism based on charge density topological interaction energies

Abstract: The packing interactions have been evaluated in the context of the self-assembly mechanism of crystal growth and also for its impacts on the aromaticity of the trimesate anion. The structure of ethylammonium trimesate hydrate (1) measured at 100 K and a charge density model, derived in part from theoretical structures, is reported. Theoretical structure factors were obtained from the geometry-optimized periodic wave function. The trimesic acid portion of 1 is fully deprotonated and participates in a variety hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…The formation of a cocrystal has to be an energetically favored process, of course. Hence, the use of various theoretical methods can be helpful, especially in the analysis of hydrogen-bonding motifs and synthon energies in the crystalline phases based on various approaches. However, the thermal stability of a resulting multicomponent phase does not necessarily need to be greater than the pure components. Indeed, a recent analysis of pharmaceutical cocrystals based on literature searching showed that more than 85% of such cocrystal systems have melting points between or lower than their corresponding pure mere components …”
Section: Introductionmentioning
confidence: 99%
“…The formation of a cocrystal has to be an energetically favored process, of course. Hence, the use of various theoretical methods can be helpful, especially in the analysis of hydrogen-bonding motifs and synthon energies in the crystalline phases based on various approaches. However, the thermal stability of a resulting multicomponent phase does not necessarily need to be greater than the pure components. Indeed, a recent analysis of pharmaceutical cocrystals based on literature searching showed that more than 85% of such cocrystal systems have melting points between or lower than their corresponding pure mere components …”
Section: Introductionmentioning
confidence: 99%